USAHA PRODUKSI LE-MUSH (LEMPENG MUSHROOM) DARI JAMUR TIRAM SEBAGAI MAKANAN ALTERNATIF MSG (MURAH, SEHAT, DAN GIZI TINGGI) - Yustari, Erik; Sridevi, Heza; Rahmah, Elysa Aulia; Sodiqin, Muhammad (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
Banjar Plates is a very well known Banjarmasin communities in Southern Borneo region but not yet have a sale value. Based on facts, oyster mushroom contains some nutritions for our health. But, in culinary industry oyster mushroom is really few. Actually, oyster mushroom is just made for soup or additional ingridients for beverage and this thing make oyster mushroom has less value for society. In this part, we made a new kind of food from oyster mushroom that is delicious, interesting, and innovative plate and also has more usage for society. Mushroom plate has 2 main flavours, chilly and sweet. Each of flavour, we also made some variant flavours, original, cheese, sausage, beef shredded, chicken shredded, cheese + sausage, and also has a good price Rp6.000,00 for original, Rp7.000,00 for cheese, sausage, beef shredded, Rp8.000,00 for chicken shredded and cheese + sausage. Our marketing method is selling alongside of the road or in a store and the customer that want to buy just choose the variant and wait for 5 minutes and Plate is ready to serve in place or their could take home.After we sold it for 4 months, we realized that the customer really appreciated our product. This thing also supported by the chart that always grew up for each month. And finally, we really sure that this product will be famous in the future. Keywords: Oyster mushroom, variant, innovative, nutrition